Immunohistochemistry of the Human Adrenal CYP11B2 in Normal Individuals and in Patients with Primary Aldosteronism - Gomez-Sanchez, Celso E.; Gomez-Sanchez, Elise P.; Nishimoto, Koshiro (Hormone and Metabolic Research, 2020)
The CYP11B2 enzyme is the terminal enzyme in the biosynthesis of aldosterone. Immunohistochemistry using antibodies against CYP11B2 defines cells of the adrenal ZG that synthesize aldosterone. CYP11B2 expression is normally stimulated by angiotensin II, but becomes autonomous in primary hyperaldosteronism, in most cases driven by recently discovered somatic mutations of ion channels or pumps. Cells expressing CYP11B2 in young normal humans form a continuous band beneath the adrenal capsule; in older individuals they form discrete clusters, aldosterone-producing cell clusters (APCC), surrounded by non-aldosterone producing cells in the outer layer of the adrenal gland. Aldosterone-producing adenomas may exhibit a uniform or heterogeneous expression of CYP11B2. APCC frequently persist in the adrenal with an aldosterone-producing adenoma suggesting autonomous CYP11B2 expression in these cells as well. This was confirmed by finding known mutations that drive aldosterone production in adenomas in the APCC of clinically normal people. Unilateral aldosteronism may also be due to multiple CYP11B2-expressing nodules of various sizes or a continuous band of hyperplastic ZG cells expressing CYP11B2. Use of CYP11B2 antibodies to identify areas for sequencing has greatly facilitated the detection of aldosterone-driving mutations.
Keywords: aldosterone; immunochemistry; aldosternism